Cancer cell-intrinsic resistance to BiTE therapy is mediated by loss of CD58 costimulation and modulation of the extrinsic apoptotic pathway. Issue 3 (16th March 2022) - Shen, Ye; Eng, Jason S; Fajardo, Flordeliza; Liang, Lingming; Li, Cong; Collins, Patrick; Tedesco, Donato; Nolan-Stevaux, Olivier
Abstract : Background: Bispecific T-cell engager (BiTE) molecules induce redirected lysis of cancer cells by T cells and are an emerging modality for solid tumor immunotherapy. While signs of clinical activity have been demonstrated, efficacy of T-cell engagers (TCEs) in solid tumors settings, molecular determinants of response, and underlying mechanisms of resistance to BiTE therapy require more investigation. Methods: To uncover cancer cell-intrinsic genetic modifiers of TCE-mediated cytotoxicity, we performed genome-wide CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) loss-of-function and CRISPRa (CRISPR activation) gain-of-function screens using TCEs against two distinct tumor-associated antigens (TAAs). By using in vitro T-cell cytotoxicity assays and in vivo efficacy studies, we validated the roles of two common pathways identified in our screen, T-cell costimulation pathway and apoptosis pathway, as key modifiers of BiTE activity. Results: Our genetic screens uncovered TAAs-independent cancer cell-intrinsic genes with functions in autophagy, T-cell costimulation, the apoptosis pathway, chromatin remodeling, and cytokine signaling that altered responsiveness to BiTE-mediated killing. Notably, loss of CD58 (the ligand of the CD2 T-cell costimulatory receptor), a gene frequently altered in cancer, led to decreased TCE-mediated cytotoxicity, T-cell activation and antitumor efficacy in vitro and in vivo. Moreover, the effects of CD58 loss were synergistically compounded by concurrent loss of CD80/CD86 (ligands for the CD28 T-cell costimulatory receptor), whereas joint CD2 and CD28 costimulation additively enhanced TCE-mediated killing, indicating non-redundant costimulatory mechanisms between the two pathways. Additionally, loss of CFLAR (Caspase-8 and FADD Like Apoptosis Regulator), BCL2L1, and BID (BH3 Interacting Domain Death Agonist) induced profound changes in sensitivity to TCEs, indicating that key regulators of apoptosis, which are frequently altered in cancer, impact tumor responsiveness to BiTE therapy. Conclusions: This study demonstrates that genetic alterations central to carcinogenesis and commonly detected in cancer samples lead to significant modulation of BiTE antitumor activity in vitro and in vivo, findings with relevance for a better understanding of patient responses to BiTE therapy and novel combinations that enhance TCE efficacy.